EFEKTIVITAS FINANACIAL DISTRESS DAN KOMITE AUDIT TERHADAP AUDIT DELAY DENGAN OPINI AUDIT SEBAGAI VARIABEL MODERASI PADA PT GARUDA INDONESIA Tbk - Baviga, Rio (Gapenas Publisher, 2024)
This study aims to examine the effect of Financial Distress and the Audit Committee on Audit Delay, with Audit Opinion as a moderating variable at PT Garuda Indonesia from 2014-2023. This research is a quantitative study with a descriptive approach. The dependent variable in this study is Audit Delay, measured by Time Interval. The independent variables are Financial Distress and the Audit Committee, measured by the Debt to Asset Ratio (DAR) and the number of audit committee members, respectively. The moderating variable is Audit Opinion, measured with a Dummy Variable. The research methodology used includes multiple linear regression and Moderated Regression Analysis (MRA) using SPSS version 24. Based on the results of the research conducted, the conclusions that can be drawn are: Financial Distress has a negative and significant effect on Audit Delay, the Audit Committee has a negative and significant effect on Audit Delay, Audit Opinion does not moderate the effect of Financial Distress on Audit Delay, and Audit Opinion does not moderate the effect of the Audit Committee on Audit Delay